IMMUNE EVASION OF MYCOPLASMA - AJI NARJISS (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2023)
Mycoplasmas are a group of bacteria that can cause a range of human diseases affecting various body systems, including the respiratory, urogenital, musculoskeletal, central nervous, and cardiovascular systems. Unlike other prokaryotes, mycoplasmas have a small genome and limited biosynthetic capabilities. Moreover, they lack a cell wall and instead have a plasma membrane composed of cholesterol and glycolipids. This characteristic enables them to evade the host's immune response. Mycoplasmas have virulence factors that allow them to invade and survive within host cells, triggering inflammation and clinical manifestations. Once inside the host cell, mycoplasmas can lead to cell death or dysfunction. This, in turn, elicits an inflammatory response, causing the clinical manifestations of mycoplasma infections. The treatment of mycoplasma infections depends on the specific bacterial species involved and the severity of the infection. Antibiotics are typically used to treat these infections. However, some mycoplasma species are resistant to traditional antibiotics, necessitating alternative treatments. Macrolide antibiotics are commonly used as first-line treatments for most mycoplasma infections, but other antibiotics may be necessary based on the resistance profile of the bacteria. Mycoplasmas have several mechanisms that enable them to evade the host immune response, such as altering the composition of their cell membrane to prevent recognition by host immune cells, secreting proteins that inhibit immune cell function, and inducing host cells to produce cytokines that suppress the immune response. Hence, understanding their clinical manifestations, pathophysiology, and treatment options is crucial for managing and preventing these infections. In conclusion, mycoplasmas are a unique group of bacteria responsible of various human diseases. Their ability to evade the host immune response and their resistance to traditional antibiotics make their treatment challenging. However, by gaining a better understanding of their virulence factors and mechanisms of immune evasion, we can develop more effective treatments for these infections.
Keywords: Mycoplasma pneumoniae; Ureaplasma urealyticum; Mycoplasma hominis; Mycoplasma genitalium; Immune evasion; Mycoplasma Pneumoniae; Ureaplasma Urealyticum; Mycoplasma Hominis; Mycoplasma genitalium; immune evasion